Hubungan Teknik Menyusui dengan Kejadian Regurgitasi pada Bayi Usia 0-6 Bulan di Posyandu Desa Kemulan - Elfa Rahmawati Rifamad; Sulistiyah Sulistiyah (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Regurgitation, or spitting up, is a common condition in infants caused by the immaturity of the digestive system, particularly the lower esophageal sphincter muscle. One contributing factor to regurgitation is improper breastfeeding techniques. This study aims to analyze the relationship between breastfeeding techniques and the incidence of regurgitation in infants aged 0–6 months by comparing two groups: a control group and an intervention group that received education on proper breastfeeding methods. This research employed a descriptive quantitative design with a comparative approach involving two independent groups. A total of 40 mothers were selected using total sampling. Data were collected through structured questionnaires and analyzed using the Independent Sample T-Test with SPSS version 22. The results showed a significant difference between the control and intervention groups in terms of regurgitation incidence, with a significance value of p = 0.005 (p < 0.05). Mothers who practiced proper breastfeeding techniques were more likely to have infants with milder or no regurgitation. In conclusion, there is a significant relationship between breastfeeding techniques and the incidence of regurgitation in infants, indicating the importance of providing breastfeeding education as a promotive and preventive measure.